Bioconversion of L-phenylalanine to 2-phenylethanol by the novel stress-tolerant yeast Candida glycerinogenes WL2002-5. Issue 6 (1st November 2016) - Lu, Xinyao; Wang, Yuqin; Zong, Hong; Ji, Hao; Zhuge, Bin; Dong, Zhuoli
ABSTRACT: 2-Phenylethanol (2-PE) is a high value aromatic alcohol with a rose-like odor that is utilized in the cosmetics and other industries. Although the chemical routes of 2-PE production have been altered by some microbial transformation processes, the poor tolerance to organic solvents of these microorganisms has limited the 2-PE yield. In this study, the stress-tolerant yeast Candida glycerinogenes WL2002-5 showed a 2-PE tolerance to 4 g/l, which is the highest reported to date. Moreover, the 2-PE titer in a batch fermentation fromL -phenylalanine reached 5g/l, which is the highest level achieved by fermentation without in situ product recovery. These results suggest C. glycerinogenes WL2002-5 is a robust strain for the bioproduction of 2-PE with potential for commercial exploitation.